Molecular analysis of Acanthemblemaria macrospilus (Teleostei: Chaenopsidae) with description of a new species from the Gulf of California, Mexico - Lin, Hsiu-Chin; Galland, Grantly R. (Zootaxa, 2010)
Molecular analysis of the chaenopsid tube blenny, Acanthemblemaria macrospilus Brock, reveals species-level differentiation and the existence of a new species, described here as Acanthemblemaria hastingsi, using molecular and morphological data. This new species is a member of the hancocki species group and is limited to the Gulf of California. It is distinguishable from A. macrospilus by mitochondrial gene sequences of cytochrome C oxidase I and D-loop region as well as by coloration. This differentiation is also supported to a lesser extent by the nuclear ribosomal protein S7 first intron. There is no geographic overlap in the ranges of these species, as they occur exclusively on either side of the Sinaloan Gap.